Spirit bound - Mead, Richelle (New York, N.Y. : Razorbill, 2010)
Rose Hathaway has finally returned to St. Vladimir's and to her best friend, Lissa. But Rose's heart still aches for Dimitri, and she knows he's out there, somewhere. He has tasted her blood, and now he is hunting her. Only this time, he won't rest until Rose joins him--forever.
Keywords: Vampires -- Juvenile fiction; Schools -- Juvenile fiction; High schools -- Juvenile fiction; Supernatural -- Juvenile fiction; Friendship -- Juvenile fiction; Interpersonal relations -- Juvenile fiction